Arv Adherence as the Main Predictor of Viral Load Levels: A Case Study at Pasar Minggu Health Center - Yunita Sri Ulina Sitepu; Dewi Purnamawati; Nurfadhilah Nurfadhilah (Advances In Social Humanities Research, 2026)
This study aims to analyze the effectiveness of adherence to antiretroviral (ARV) therapy on viral load levels among People Living with HIV (PLHIV) in the working area of the Pasar Minggu Health Center. The study employed a cross-sectional design with a total sample of 80 PLHIV. Data were obtained from medical records and a validated adherence questionnaire. Analysis was performed using Chi-square tests and multivariate logistic regression. The results showed that ARV adherence had a significant effect on viral load levels (p = 0.001; Exp(B) = 0.045), where non-adherent individuals had a 22-times higher risk of having a detectable viral load. The duration of HIV diagnosis was also significant (p = 0.006; Exp(B) = 0.086), while comorbidities were not statistically significant (p = 0.078) but clinically relevant (Exp(B) = 8.696). Both variables acted as confounders in the relationship between adherence and viral load. The study concludes that ARV adherence plays a crucial role in reducing viral load. Comorbidities and the duration of HIV diagnosis influence adherence and should be considered in therapeutic interventions. Education-based, counseling, and family-support interventions need to be strengthened to improve long-term adherence.